La fiebre del carbón - O'Dell, Tawni (Nuevos tiempos (Madrid, Spain), 2013)
Coal mining community deputy Ivan Zoschenko remembers the injury that ended his football career, prepares for a former teammate's release from prison, and confronts a secret that has troubled his conscience.